Tourism Experience Economy, Tourist Engagement, & Overall Satisfaction in Creating Incentive to Share by Word of Mouth (WOM) among Foreign Tourists in Pinge Tourism Village, Bali, Indonesia - Darmateja, I Made Sugita; Surata, I Ketut; Kencana, I Putu Eka Nila (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2025)
This study is aimed at analyzing the effect of tourism experience economy, tourism engagement, & overall satisfaction in creating an incentive to share word of mouth (WOM) among foreign tourists in Pinge Tourism Village, Bali, by applying the hierarchical model construct. Data from a sample of 41 respondents were collected within the research period from August to December 2019 to be used in the analysis of causal relationships. In this research model, tourism experience economy and tourist engagement are posited as second-order constructs that theoretically would affect the overall satisfaction as an antecedent of creating incentive for word of mouth (WOM). In the structural model analysis, the results found were that of tourism experience economy construct has significant effect to overall satisfaction with a coefficient value of 0.666; and overall tourist satisfaction also has significant, positive effect to the foreign tourists' incentive to share word of mouth (WOM) in Pinge Tourism Village, with path coefficient value of 0.497.